Does Conservation Agriculture Work For Rainfed Farming In Nepal? A Review (Agronomy Journal of Nepal, 2021)
Intensive tillage-based agricultural practices severely affect the soil’s physical, chemical and biological properties that eventually limit the crop yields in longer run. It is due to declining soil physical, chemical and biological properties. Several studies have been done to restore and improve the soil quality, however conservation agriculture (CA)-based practices of minimum tillage, crop residue retention and appropriate crop rotations has been observed to be promising across the globe. Studies on CA under Nepal’s rainfed farming systems of Terai and hills of Nepal improved the soil quality, increased individual crop and system yields, reduced labor demand and was economically profitable. However, lack of adequate soil moisture during planting in initial seasons, inadequate tillage equipment and weed management options are the key constraints of rainfed farming to be transformed into CA in initial stages. In Nepal, the introduction of animal-drawn direct seeding equipment, management of residues or mulches, mechanical or herbicidal weed management options for small-scale rainfed hill farmers can be of paramount significance in scaling-out of the CA based practices in Nepal. For this, further on-station and on-farm verifications of CA based practices need to be carried out across the various cropping systems and agro[1]ecological regions of the country by Nepal Agricultural Research Council (NARC), Nepal in collaboration with international CG centers, universities, extension and development institutions.